Games for dead girls : a thriller - Williams, Jen (Fiction writer) (Crooked Lane, 2023)
"For Charlie and her niece Katie, it's supposed to be a quiet holiday in the peaceful, out-of-the-way seaside town of Hithechurch, England. Charlie is researching a book on the folklore of the area, and the gloomy sea and dangerous caves seem to offer up plenty of material, while Katie is just there to run wild and get some fresh air. But Charlie's research reveals a deeper, darker secret, one that uncovers her own, carefully hidden past. Because young women are going missing again: a teenage girl snatched from the beach in broad daylight, and before that, other girls through the decades have vanished from the area, their families left with no answers and no bodies to bury. Charlie's creation was a thing of felt, straw, fury, and a rusty pair of scissors in the dark. It couldn't be her monster. Could it? Charlie is set on discovering the truth about the girls' disappearances, but she's about to encounter a force of pure, obsessive malevolence that threatens to destroy anything in its path." --